Implementasi Tungku Pembakaran Sampah Minim Asap Proker Mahasiswa Teknik Sipil UNA Sebagai Solusi Pengelolaan Sampah Ramah Lingkungan - Nadia Fazha; M. Dimas Andrean; Khairul Shaleh, (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Ineffective management of household waste in rural areas, such as Aek Korsik Village, Aek Ledong District, Asahan Regency, causes air pollution due to traditional waste burning practices. This research aims to design and implement an environmentally friendly low-smoke waste incinerator as an alternative solution based on simple technology and local resources. The research methods used are technological engineering approaches and field studies, including tool design, trials, and environmental and social impact evaluation. The furnace is designed using heat-resistant local materials and mild steel, features a dual ventilation system and a smoke exhaust system with a simple filter, and has a combustion capacity of 5 kilograms per cycle. Preliminary studies show that the composition of waste is dominated by organic matter (60%), plastic and paper (30%), as well as the rest are inorganic. Testing over several weeks showed that an average burn time of 1.5 hours was able to reduce smoke emissions by up to 60% compared to conventional methods. The air quality around the test site has improved significantly, and the community has responded positively to the ease of use and environmental benefits of the furnace. This study concludes that low-smoke combustion furnaces are effective as environmentally friendly waste management solutions in villages, with recommendations for increasing combustion capacity and integrating other waste management methods to support sustainability and environmental preservation.